Business Development Strategy Journaling Book (Case Study On Fill The Blankspace) - Pohan, Sheilla Yasmin Afriani; Asnawi, Yudha Heryawan; Asikin, Zenal (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to analyze the implementation of character-based learning strategies in improving students’ motivation and learning outcomes in Islamic Religious Education. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that teachers play a crucial role in shaping students’ character through modeling, habituation, and contextual approaches adapted to students’ needs. The applied learning strategies emphasize not only cognitive development but also the integration of spiritual, social, and emotional values. The main challenges in implementing these strategies include limited environmental support and inconsistency in applying character values outside the classroom. Nevertheless, through collaboration among teachers, parents, and the school environment, students’ religious character formation and learning motivation significantly improve. This research contributes to strengthening character education practices within the context of modern Islamic education.